Peran Mediasi Burnout dalam Pengaruh Emotional Exhaustion dan Work Overload Terhadap Job Performance PNS Pemerintah Daerah Provinsi Bengkulu - Rambe, Habiburrahman; Pareke, Fahrudin JS (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This study examines the role of Burnout in mediating the impact of Emotional Exhaustion and Work Overload on the Job Performance of Civil Servants in the Bengkulu Provincial Government. Using a survey of 120 civil servants and PLS-SEM analysis, it found a significant relationship between these factors. Burnout was identified as a mediator, linking stress and workload with reduced performance. The findings underscore the need for Burnout management strategies to enhance civil servants’ well-being and performance. The study validates the PLS-SEM method for understanding complex relationships in public sector work dynamics and offers insights for policy and intervention program development to improve welfare and performance.The research underscores the importance of understanding and managing Burnout among civil servants. It highlights how Emotional Exhaustion and Work Overload can significantly impact Job Performance, with Burnout serving as a critical link. The study’s findings are instrumental in shaping policies and intervention programs aimed at improving the welfare and performance of civil servants in the Bengkulu Provincial Government. By addressing Burnout, the government can enhance job satisfaction, reduce stress, and ultimately improve the quality of public services. The study also emphasizes the effectiveness of the PLS-SEM method in analyzing complex relationships within the dynamics of public sector work. This research contributes to the body of knowledge on public sector performance and provides a foundation for future studies in this area